2021
DOI: 10.1073/pnas.2024890118
|View full text |Cite
|
Sign up to set email alerts
|

A stable proportion of Purkinje cell inputs from parallel fibers are silent during cerebellar maturation

Abstract: Cerebellar Purkinje neurons integrate information transmitted at excitatory synapses formed by granule cells. Although these synapses are considered essential sites for learning, most of them appear not to transmit any detectable electrical information and have been defined as silent. It has been proposed that silent synapses are required to maximize information storage capacity and ensure its reliability, and hence to optimize cerebellar operation. Such optimization is expected to occur once the cerebellar ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…1A, C). Silent synapses were also recently observed during development and in adult rodents [24,63].…”
Section: Spatially Organized Gc-pc Connectivity Maps As An Implementa...mentioning
confidence: 75%
“…1A, C). Silent synapses were also recently observed during development and in adult rodents [24,63].…”
Section: Spatially Organized Gc-pc Connectivity Maps As An Implementa...mentioning
confidence: 75%
“…This conclusion was reached because only 7% of stimulated granule cells generated electric responses in the soma of Purkinje cells, as opposed to the expected ~54% based on the anatomical count of spines and synapses ( Napper and Harvey, 1988a ; Napper and Harvey, 1988b ). A recent study in slices also found that more than 70% of parallel fiber synapses did not produce detectable fast postsynaptic responses ( Ho et al, 2021 ). This proportion was the same in young and adolescent mice, suggesting that it is a stable feature of the cerebellum even during development ( Ho et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in slices also found that more than 70% of parallel fiber synapses did not produce detectable fast postsynaptic responses ( Ho et al, 2021 ). This proportion was the same in young and adolescent mice, suggesting that it is a stable feature of the cerebellum even during development ( Ho et al, 2021 ). In short, there is evidence that perhaps only around 10–20% of parallel fiber synapses may be eloquent, that is, capable of eliciting currents in the soma of Purkinje cells.…”
Section: Discussionmentioning
confidence: 97%
“…This conclusion was reached because only 7% of stimulated granule cells generated electric responses in the soma of Purkinje cells, as opposed to the expected ∼ 54% based on the anatomical count of spines and synapses (Napper and Harvey, 1988b, a). A recent study in slices also found that more than 70% of parallel fiber synapses did not produce detectable fast postsynaptic responses (Ho et al, 2021). This proportion was the same in young and adolescent mice, suggesting that it is a stable feature of the cerebellum even during development (Ho et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in slices also found that more than 70% of parallel fiber synapses did not produce detectable fast postsynaptic responses (Ho et al, 2021). This proportion was the same in young and adolescent mice, suggesting that it is a stable feature of the cerebellum even during development (Ho et al, 2021). In short, there is evidence that perhaps only around 10 to 20% of parallel fiber synapses may be eloquent, that is, capable of eliciting currents in the soma of Purkinje cells.…”
Section: Branched Synapses As Eloquent Synapses?mentioning
confidence: 99%